Peranan Hatobangon Dalam Penyelesaian Kekerasan Dalam Rumah Tangga (KDRT) di Kabupaten Padang Lawas - Harahap, Holilatun Nisa; Syahminan, Mhd.; Muary, Rholand (Media Hukum Indonesia (MHI), 2024)
This research aims to find out what role hatobangon plays in resolving domestic violence in the Sigading village community, Huristak District, Padang Lawas Regency. This research uses qualitative research methods with a descriptive approach. Data collection techniques used were observation, interviews and documentation. The number of informants in this research was eight people. This research uses Lewis Coser's theory, namely social conflict theory. According to Coser, conflict can play an important role in the development, consolidation, and maintenance of social structures. He sees conflict as a struggle over values and claims for status, power, and scarce resources with the goal of neutralizing opponents or eliminating rivals. Coser differentiates conflict into two, namely realistic conflict is conflict that originates from individual or community group disappointment with the demands that exist in social relations. Meanwhile, non-realistic conflict is conflict that does not originate from opposing competitive goals, but is a need for certain parties to reduce tension. Hatobangon is a traditional figure who participates in resolving problems, if invited by the family to mediate. In the Qur'an, it is explained that if there is a dispute between husband and wife, then call the hakam as a mediator who will consider both cases and prevent people from being wronged.